PENGEMBANGAN BIOREAKTOR HIDROLISIS ENZIMATIS UNTUK PRODUKSI BIOETANOL DARI BIOMASSA JERAMI PADI - Diyono Ikhsan; Mohamad Endy Yulianto; Indah Hartati (JURNAL LITBANG PROVINSI JAWA TENGAH, 2009)
Human activity in modern life has disturbed air composition and causes many problems dealing with environmental issues such as acid rain and global warming. Carbon dioxide is a greenhouse gas, which the concentration in the air is increasing by 30% since the era of industrial revolution. Some activities, especially the usage of fossil fuel has cause the increasing of carbon dioxide concentration and other greenhouse gasses. When fossil fuels are consumed, carbon sequestered from the global carbon cycle for millions of years is released into the atmosphere, where it accumulates. One of effort need to be taken is to replace the usage of fossil fuel by bio-ethanol. Bio-ethanol consumption can release considerably less CO2 depending on how it is produced. Ethanol from cellulosic biomass could dramatically reduce emissions of the greenhouse gas, carbon dioxide (CO2). Although burning gasoline and other fossil fuels increases atmospheric CO2 concentrations, the photosynthetic production of new biomass takes up most of the carbon dioxide released when bio-ethanol is burned. Rice straw hydrolysis for the enzymatic production of ethanol has some benefits such as higher yield, minimum side reaction, lower energy consumption and lower operation condition. The research objective was to determine the optimum condition of rice straw hydrolysis process for bio-ethanol production by using Trichordema reseei. The research was divided into several research steps which were bioreactor fabrication, optimization of hydrolysis process parameters, mathematical modeling by regression analysis and glucose fermentation process. Optimization process was conducted by using 2n factorial design. Parameters studied in this research were substrate-enzyme ratio, water-rice straw ratio, pH and reaction time. From each variable we analyzed the glucose qualitatively and quantitatively. The determination of the most affecting variables was conducted by normal probability plot analysis. The calculation of main and interaction effect was conducted prior. The process variables that affect the rice straw hydrolysis process were pH and substrate-enzyme ratio. The optimum condition was achieved at enzyme-substrate ratio 1:1,4; where the glucose yield was 18,001% and the mathematical model was: . The optimum pH was hydrolysis process at pH 4,2 and the mathematical model was .